SISTEM MONOPOLI MENURUT PANDANGAN YUSUF QARDHAWI DALAM KITAB HALAL HARAM FIL ISLAM DITINJAU DALAM PERSPEKTIF EKONOMI SYARIAH - Alti Pidola, Viras; Arfah; Nurhaida (Journal of Islamic Economic and Law (JIEL), 2024)
The Monopoly System According to Yusuf Qardhawi’s Perspective in the Book Halal wa Haram fil Islam. The concept found in this study is that monopoly can be either permissible or impermissible. Thus, there is a distinction between monopoly and hoarding. In Islam, storing goods for inventory purposes is not considered haram as long as it does not disrupt market mechanisms. This study employs library research, which is conducted using literature sources such as books, journals, notes, and reports from previous studies. Therefore, this type of research aims to examine the ideas, perspectives, and views on monopoly as expressed by Yusuf Qardhawi in his book Halal wa Haram fil Islam. The results of this study explore Yusuf Qardhawi’s view on monopolistic practices and how monopoly is perceived within Islamic economics. According to Yusuf Qardhawi, monopoly involves withholding goods from market circulation to raise prices. He prohibits monopolizing all essential human needs and states that this prohibition applies at all times, without distinguishing between times of scarcity and times of surplus. The study concludes that monopoly practices are acts that are forbidden and haram in Islam, as such practices can harm society by potentially causing economic crises and making essential goods difficult to obtain. However, in Islam, the concept of hoarding for the benefit of the ummah is permissible by scholars—provided that the goods are sold at fair prices.